2003
DOI: 10.1063/1.1540617
|View full text |Cite
|
Sign up to set email alerts
|

Trapped metastable anions in low-energy electron scattering from C20 clusters

Abstract: Use of complex configuration interaction calculations and the stationary principle for the description of metastable electronic states of HCl − J. Chem. Phys. 133, 044305 (2010); 10.1063/1.3467885 Low-energy electron scattering by cubane: Resonant states and Ramsauer-Townsend features from quantum calculations in the gas phase One-electron resonances and computed cross sections in electron scattering from the benzene moleculeCalculations are reported on scattering resonances in low-energy electron collisions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Similarly, fullerenes have also been synthesized from small diameter C20 to giant C266 [15][16][17][18][19][20]. The fullerenes smaller than C60 have been reported in the gas phase experiments due to their higher chemical reactivity [21][22][23][24][25][26][27][28][29][30][31][32][33]. C36 has been predicted as one of the magic number small fullerene detected by mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, fullerenes have also been synthesized from small diameter C20 to giant C266 [15][16][17][18][19][20]. The fullerenes smaller than C60 have been reported in the gas phase experiments due to their higher chemical reactivity [21][22][23][24][25][26][27][28][29][30][31][32][33]. C36 has been predicted as one of the magic number small fullerene detected by mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1,16 Theoretical attempts to characterize C 20 clusters have been reported by several groups. 4,5,17,18 Similar structural alternatives arise for C 24 , and the latest calculations indicate that D 6 symmetry is the most stable for C 24 . [19][20][21][22] C 28 was originally reported by Kroto in 1987 14 and the tetrahedral symmetry of C 28 was shown to be the most stable at the SCF level.…”
Section: Introductionmentioning
confidence: 83%
“…The synthesis of low-mass fullerenes C n ( n < 60) on a macroscopic scale is an active field of current investigation . A number of smaller fullerenes C n ( n < 60) have been detected by mass spectroscopic methods in the gas phase and numerous theoretical calculations have been performed to characterize them. Kroto suggested that fullerenes C n with magic numbers n = 24, 28, 32, 36, 50, 60, and 70 should have enhanced stability relative to those with similar numbers of atoms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometrical structures of the fullerenes are obtained using the density-functional tightbinding method [27], which allows for efficient quantum simulations of molecular systems containing several hundreds or thousands of atoms; the ionization potentials are taken from Refs. [28,29]. Indeed, as compared in Fig.…”
mentioning
confidence: 85%